Providing open access to PhD theses: visibility and citation benefits. Issue 4 (6th September 2016) - Ferreras-Fernández, Tránsito; García-Peñalvo, Francisco; Merlo-Vega, José A.; Martín-Rodero, Helena
Abstract : Purpose: The purpose of this paper is to report the benefits of scientific communication model of open access (OA) repositories to e-theses. Specifically, the study focusses on the benefits of accessibility, dissemination, visibility and impact of PhD e-theses deposited in repositories. Design/methodology/approach: The study analysed a random sample of 125 PhD e-theses deposited in an OA repository, specifically in the institutional repository (IR) of the University of Salamanca (Gredos). It tracked the sample for analysing on one side the visits and downloads of the e-theses, whose data are obtained from the statistics module of the repository, and on the other side the data citation provided by Google Scholar Citation on these e-theses. To analyse the differences between the indicators (visits, downloads and citations) in different knowledge areas, the Kurskall-Wallis test has been used. Findings: The results indicate that OA IRs become an advantageous channel of scientific communication to grey literature like dissertations and PhD theses, because it increases visibility and use and also produces a significant citation rate. Originality/value: The paper uses metrics that are used in IR to measure the visibility and impact of a type of grey literature that is very difficult to track because it is unpublished. The dissemination of the grey literature through OA repositories makes it possible. The value of the work lies in the empirical evidence obtained from the analysed PhD e-theses of Gredos repository.